The Right of Concerned Persons in the Personal Data Process: Some Legal Notes on France and Europe (Law, State and Telecommunications Review, 2018)
Purpose ”“ This study aims to verify how the European and French legislation give the protection of personal data over concerned persons. Thus, some notes are written about legal concepts related to this protection, involving the rights’ subject and their content. Methodology/approach/design ”“ This analysis focuses on the General Data Protection Regulation (GDPR) and the French Statute to Promote a Digital Republic. Therefore, through a legal analysis, it is made a reflection of the purpose and approaches of certain rights, encompassing both the actual rights’ subject, which involves informational self-determination, and the legal representation of concerned persons in the data processing, and the content of such rights, which includes traditional rights and new ones. Findings ”“ Concerning to the rights holders, it is made a relation of normative self-determination as a principle present in the analyzed statutes (even implicitly), as well as the importance of representing the person concerned regarding the minor and the deceased. For the content of the rights, the right to information is present, which, in turn, allows for openness to other rights (such as rectification and erasure); and there is mention of the conditions under which the right to forgetfulness and portability of data can be applied regarding new rights. Practical implications ”“ This study brings to the scientific sphere the debate on the protection of personal data. From the analysis of the European legal procedures, one can have them by reference and studies for other countries. Originality/value ”“ The originality is in the comparison of the treatment conferred by the European and French statutes of the rights relative to the protection of personal data.